SURFACE FIXATION A NEW METHOD OF DETECTING CERTAIN IMMUNOLOGICAL REACTIONS - RUIZ CASTANEDA, MAXIMILIANO (HOSPITAL GENERAL, LABORATORIO DEL TIFO, CD. MEXICO, DF, MEX, 1977)
Nerve cells at the margin of cerebral necrosis show a marked increase in protoplasmic lipoids, evidently a precursor of cellular degeneration Three staining methods provide a means of characterizing the pathological lipoids in cerebral necrosis Scarlet
PROC SOC EXP BIOL MED
Keywords: SURFACE, FIXATION, IMMUNOLOGICAL, REACTIONS; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA EXPERIMENTAL